Evaluating the Accessibility of Computer Laboratories, Libraries, and Websites in Jordanian Universities and Colleges - Abu Doush, Iyad (2018)
This article evaluates the accessibility computer laboratories, libraries, and web sites of five different institutions of higher education in Jordan. The evaluation is performed using a questionnaire and by expert visiting these institutions of higher education to check their accessibility according to a set of universal standard collected from the literature. The analysis of the results revealed a serious weakness in understanding, adopting and implementing web accessibility guidelines throughout nearly all evaluated Jordanian universities and colleges. On the other hand, the accessibility of computer laboratories and libraries the questionnaire answers show that there is environmental barrier and technological barrier for persons with disabilities to access such services. The article points out the importance of improving awareness, training staff and developers, and developing formal guidelines to improve the accessibility of universities and colleges services.